History and its image in recent Czech prose - Vanicek, Jakub (Bohemica Olomucensia, 2020)
After 1989, the critical discussion in Czech literature went through several important stages regarding the relation between a work of art and social events. Based on this discussion, the presented paper examines the relations between the literary work and its critical reflection and tries to define the ``type of social speech production''. The starting point for this search is the reasoning by Pierre Macherey, who argues that a literary work is always related to history in some way. The following section of the paper provides the interpretations of the novels by David Zabransky and Vaclav Kahuda.
Keywords: historical novel; social novel; literary criticism; historiographic metafiction